NOTES ON CONTRIBUTORS - Philip, Susan (SARE: Southeast Asian Review of English, 2025)
NOTES ON CONTRIBUTORS This section introduces the contributors to SARE Vol. 62, Issue 1 (2025), highlighting their diverse academic and creative backgrounds. From postgraduate students to senior scholars, their work spans comparative literature, folklore, ecocriticism, postcolonialism, indigenous storytelling, and translation, reflecting the journal’s transnational and interdisciplinary focus across Asia and beyond.